A study on awareness of household waste management in a rural area of northern Kerala - Noonhiyil Kaithery, Nivya; Karunakaran, Usha; Lakshmanan, Manju Thandayan (International Journal Of Community Medicine And Public Health, 2024)
Background: Proper waste management is a major concern of public health. It is necessary to create positive behavioural changes towards waste management among public in order to control diseases. Objective was to assess the awareness of waste management among the households of Cheruthazham Panchayat in northern Kerala. Methods: A community based cross sectional study was conducted in Cheruthazham Panchayat, under Kalliasseri block, located in Kannur district of Kerala state from June 2017 to July 2018. A total of 400 households were studied. Multistage sampling was done. Data was collected by direct interview using a pre-tested semi-structured questionnaire. Data was analyzed using SPSS software. Results: The participants responsible for the waste management in household were women. Out of the 400 participants, 83%, 11% and 6% were Hindus, Muslims and Christians respectively. Majority of them (82%) had an educational qualification of high school and above. Most of them (82.5%) were housewives. About 47% of the study population belongs to upper middle class. Their major sources of information about solid waste management were Kudumbasree class, gramasabha meetings and media. In the study, 19.2% had good knowledge, 79.2% had average knowledge and 1.5% had poor knowledge on waste management. Conclusions: Majority of the participants had above average attitude towards household waste management. Continuous awareness programmes have to be conducted on safe waste disposal and efforts should be made to sustain the supervision of household waste management.